THE IMPACT OF THE INFORMATION GAP STRATEGY ON ACQUIRING ISLAMIC CONCEPTS AMONG FIFTH GRADE STUDENTS - M. Qutaiba Hamid Mohammed Al-Dulaimi (Scholars Digest Publishing, 2023)
This study aimed to find out the effect of the information gap strategy on the acquisition of Islamic concepts among the fifth scientific grade students. In order to verify the aim of the research, the researcher put the following zero hypothesis: There is no statistically significant difference at the level (0.05) between the mean scores of the experimental group whose students study the Holy Qur’an and Islamic Education with the information gap strategy and the control group whose students study the same subject in the usual (traditional) way ,To make sure of this, the researcher chose the experimental approach as a method for his research, and the center of the district of Tikrit was determined as a place to conduct the research, where the researcher chose Ibn Al-Moatim Preparatory School for Boys as a sample for the research. The second control number (33) students, with no students failing from the sample, Equivalence was conducted by the chronological age of the students calculated in months, the rate of the last year (the first course) for the fourth scientific grade, the intelligence test "Raven", the educational level of the parents, and the test of Islamic concepts was chosen as a research tool. At the end of the experiment, the researcher used the appropriate statistical methods for the research and reached That there is a difference in favor of the experimental group and in the light of the result reached by the current research, the researcher drew several conclusions and recommended a set of recommendations and suggested a number of suggestions regarding the subject of his research.
Keywords: information gap, acquisition of Islamic concepts.